ACUAN TEORI POLITIK HUKUM KELUARGA DI INDONESIA - Karina Novian Muriani R; Nurrohman Nurrohman (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
One type of law that is expected to make a major contribution to legal reform in Indonesia is Islamic law. Islamic law is expected to provide a positive color to national law, as well as family law which is a derivative of Islamic law. From the time of the Kingdom, which was replaced by Dutch colonialism, the New Order, until now, there is legal politics that seeks to reform the law in determining choices regarding the goals and methods that will be used to regulate the social life of Muslim communities in Indonesia. In implementing Islamic law as a positive color for national law, there are theories used in the formation of Islamic law, especially family law. This article uses a qualitative descriptive data analysis type with library research data collection techniques. This article will later have a purpose and discussion point regarding the political theory of Islamic legal reference used in Indonesia which is then also used in family law.